Yusuf Khan, the rebel commandant - Hill, Samuel Charles, 1857-1926. (London : Longmans, Green and co., 1914)
Life of Muhammad Yusuf, Governor of Madura and Tinnevelly, d. 1764, during the British rule of India.
Keywords: Khan, Yusuf, -- -1764.; Governors -- India -- Madurai -- Biography; India -- History -- 18th century; Madurai (India) -- History